KAP Survey of Awareness of Physiotherapy Among Urban and Rural General Population of Gujranwala Division: Kap Survey of Awareness of Physiotherapy - Asghar, Nadeem; Awais, Muhammad; Gulzar, Khushboo; Mansha, Hamza; Islam, Farooq; Tanveer, Hamza (Pakistan Journal of Health Sciences, 2022)
Physiotherapists play an important part in providing health care and physiotherapy is a recognized profession around the globe. Physiotherapy is a medical specialty that focuses on human function and mobility in order to aid people attains their full potential; It is significant to have a good understanding towards careers associated to one’s field of study. Objective: The aim of the study was to assess the awareness regarding physiotherapy among urban and rural general population in Gujranwala Division. Methods: This observational study was carried out on a sample size of 384 divided equally into 192 urban and 192 rural population of people including male and female both from age group 20 years or above through non probability random sampling. The study was carried out in general population of Gujranwala Division for 6 months. Self-made Likert scale was developed to collect data. The responses were analyzed through SPSS. Results: Out of 384 participant’s population of urban area had high knowledge attitude and practice level regarding awareness of physiotherapy whereas rural population showed moderate to low knowledge attitude and practice level. According to association between education and awareness from category Undergraduate-post graduate were highly aware of physiotherapy, while other participant’s awareness was moderate to low. Conclusions: A very good response was seen in urban population of Gujranwala Division, mostly people were highly aware of physiotherapy, whereas in rural population there was a moderate to poor response. A strong association was seen between education and physiotherapy. Higher level of education displayed powerful impact on awareness of people. Education plays an impactful role in better understanding of physiotherapy.